UJI EKSPERIMEN PEMBUATAN ”ADONAN PIZZA” BERBAHAN DASAR TEPUNG BAKAU SEBAGAI SUBTITUSI TEPUNG TERIGU - Yudy - Sunantri (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
ABCTRACT Eksperimental Test of Mangrove Flour as a Substitution of Wheat Flour in Pizza Dough Production Author: Yudy Sunantri Politeknik Bintan Cakrawala, program Studi Seni Kuliner Institusi: Politeknik Bintan Cakrawala, Program Studi Seni Kuliner Jalan Kota Kapur Kawasan Pariwisata Bintan, Lagoi Bintan Utara, Kepulauan Riau 29155 Indonesia Email: yudy.sunantri@gmail.com This eksperimental study aims to obtain a standard recipe for pizza dough and determine the feasibility of the effect mangrove fruit flour (Bruguiera gymnorrhiza) substitution on texture quality, taste and market viability, the eksperimental was conducted into 4 formulation namely TT ( 100% Wheat Flour: 0% Mangrove Flour), Tt ( 90% Wheat Flour: 10% Mangrove Flour), Tb (60% Wheat Flour: 40% Mangrove Flour), TB (Wheat Flour 40%: Mangrove Flour 60%) with fairly decent results. This data collection was done by various respondents from 40% Italian hotels / restaurants culinary professional, 30% academics, and 30% Bintan, Riau Islands residents in order to ensure the quality of innovative pizza dough from feasible basic ingredients of lindur mangrove flour. The data analysis technique was employed to determine the results and conclusions from the four formulations in the research. Based on the results and discussion, the mangrove fruit flour based pizza had good results on texture, color and market feasibility indicators, the pizza dough method from lindur mangrove flour can be mixed with wheat flour as its gluten content, because pizza dough is classified as a type of bread dough that requires gluten which highly needed for bread dough. Thus the objectives of this research is to maximize and utilize the lindur mangrove type in the Bintan island, those mangrove types are very diverse and can help small and medium enterprises (MSMEs) in Bintan to make variants of cakes and breads into culinary businesses by utilizing potential sources. Keywords: Substitution, lindur mangrove flour, feasibility, micro business